UTAUT, green values and affective factors that lead to the intention to adopt the Urban Retreat™ carpet in employees - Lekitlane, Mpho (My University, 2015)
Environmental degradation and technological advancements are two trends that are increasingly characterising the human experience. Innovation in systems to be more sustainable in relation to the environment is seen as one way to mitigate the effects of prolonged human action on the planet. Carpets in buildings have been found to be one of the biggest contributors of carbon emissions. The Interface® Urban RetreatTM carpet range has sustainable properties such as post-consumer recycled content, no volatile organic compounds and biophilic properties. The adoption of sustainable technologies, such as the Urban Retreat™ carpet, have not been instant because of the expense they are believed to incur to the organisation. In some cases, sustainable technologies have been met with outright resistance. Research into the factors leading to the adoption or acceptance of these technologies is scarce and thus of paramount importance to reduce the degradation to the planet. It is also important for employers as some sustainable technologies have been shown to be linked to positive organisational behaviours. The aim of the study was to investigate which factors led to employees having positive feelings towards the intention to adopt the Urban Retreat™ Carpet. The factors that were considered were functionality, concern for the natural environment and affectivity. These factors were investigated by means of an online survey. The functionality aspects were operationalised through the use of the Unified Theory of Acceptance of Use of Technology (UTAUT) (Venkatesh, Morris, Davis & Davis, 2003). The current research proposed that age and gender would moderate the relationship between the UTAUT factors and the feelings towards the intention to adopt. Concern for the natural environment was measured through a self-developed subscale. Finally, affect or biophilic tendencies was measured through the Nature Relatednedness scale (Nisbet, Zilenski & Murphy, 2009). The intention of the study was to determine whether the affective/biophilic properties of the carpet as well as the individual were an important determinant of the likelihood to adopt the carpet in relation to other aspects such as functionality and therefore whether the affective properties might be leveraged to encourage the acceptance of products that are more sustainable. The sample was 114 employees in a law firm in Johannesburg, considering moving from a non-biophilic range to the Urban Retreat™ range. The main analysis that was performed on the data was a multiple moderated linear regression, which assessed which independent variables explained the most amount of variance in the outcome variable. The findings show that the significant predictor of the positive feelings towards adoption were performance perception and perceived facilitating conditions. The impact of age and gender as moderator variables on these relationships was non-significant. Every effort was made to ensure that all ethical standards were met.
A research project submitted to the Faculty of Humanities, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements of the Degree of Masters of Arts (Organisational Psychology), February 2015